P140 How important is Mycobacterium Chimaera isolation in patients who have not had cardiac surgery?. (12th November 2019) - Kamalanathan, M; Perrin, F; Somasunderam, D; Breen, R
Abstract : Introduction: There have been increasing reports of invasive infection caused by Mycobacterium Chimaera in recent years. Most commonly infection has been associated with the use of heater-cooler units in open cardiac surgery. 1 Although for many clinicians M. chimaera is a new entity, it is in fact a member of the Mycobacterium avium-intracellulare complex (MAC). Limited data exist surrounding its clinical manifestations in other patient groups. Objective: To investigate the clinical characteristics of patients identified with M.Chimaera in two teaching hospitals in South-East London. Methods: All reported positive mycobacterial cultures between January 2015 to July 2019 were retrospectively searched and those where M.Chimaera was isolated were identified. Electronic patient records were reviewed for site of infection, co-morbidities, co-existing immunosuppression and clinical outcomes. 12 patients with Cystic Fibrosis and 2 paediatric cases were excluded. Results: Isolates were identified from 22 patients; 12 (55%) were male and age ranged from 21 – 83 years. The details of the cases are shown in Table 1. 2 cases (9%) had previously undergone cardiac surgery: 1 had disseminated infection that was thought related to the surgery that required treatment, while the other had an isolated sputum culture post-operatively that was not followed up. In 7 (36%) cases the positive culture was not referenced in the medical records. In one case M.Chimaera was referred to as 'a contaminant' and in another as 'likely not pathogenic.' Conclusions: M.Chimaera was only identified in our cohort from March 2018, which likely reflects the introduction of distinct speciation of M.Chimaera by the Mycobacterial Reference Laboratory. Although two of our cases had undergone cardiac surgery, the majority of our patients had underlying COPD, bronchiectasis or immunosuppression, which are similar characteristics to those found in MAC infection. We believe further studies to determine the clinical significance and outcomes of M.Chimaera infection are required. Our data also suggest that clinicians may not be aware of the clinical relevance of newly reported non-tuberculous mycobacteria, something which will become increasingly relevant in the era of routine whole genome sequencing. Reference: Ingen, et al . Global outbreak of severe Mycobacterium chimaera disease after cardiac surgery: a molecular epidemiological study. The Lancet 2017;17:10.